2013
DOI: 10.1016/j.puhe.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported general health and Body Mass Index: a U-shaped relationship?

Abstract: Objectives:A sizable literature demonstrates an increased likelihood of self-reported poor health with increasing Body Mass Index (BMI). A U-shaped relationship between BMI and health is evident in research but we do not believe the health of people who are underweight gets the attention it deserves. We investigate the relationship between BMI categories and poor general health including those persons who are underweight.Study design: Cross-sectional study Methods:Data were obtained from the Health Survey for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
2
7
1
Order By: Relevance
“…Also, in the present study underweight men and women displayed elevated levels of mental distress comparable to that of obese and severely obese individuals. These results (Table 2) are in line with prior research showing a U-shaped relation between BMI and common mental disorders [3, 2830] suggesting that both underweight and obese individuals experience more mental distress compared with their normal weight and overweight counterparts. Prior research has suggested several reasons for the elevated mental distress observed in obese individuals including stigmatization, social undesirability, and dissatisfaction with appearance.…”
Section: Discussionsupporting
confidence: 90%
“…Also, in the present study underweight men and women displayed elevated levels of mental distress comparable to that of obese and severely obese individuals. These results (Table 2) are in line with prior research showing a U-shaped relation between BMI and common mental disorders [3, 2830] suggesting that both underweight and obese individuals experience more mental distress compared with their normal weight and overweight counterparts. Prior research has suggested several reasons for the elevated mental distress observed in obese individuals including stigmatization, social undesirability, and dissatisfaction with appearance.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the BMI is a variable that interacts with several factors, including heredity, physical activity, inflammation, sleep and circadian rhythm, stress, and meals, and cannot be explained only by one factor. Many studies, however, either combine the underweight with the normal weight category or do not report or highlight results from the underweight group (13). In other words, both underweight and overweight categories are associated with a healthy lifestyle (26).…”
Section: Discussionmentioning
confidence: 99%
“…Since the connections between BMI and appearancebased social anxiety have only been mediated by body image dissatisfaction, and the model of these relationships emerged as the best-fitting model compared to a plausible alternative model, and the relationship between BMI and health-related behavior has been identified (13), changes in each variable may cause changes in other variables.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies exploring the association between BMI and SRH, some have found U shaped relationship between them [23,24], some studies have proved that BMI and SRH varies significantly across ages and sexes [25]. However, Chinese research in this field is insufficient.…”
Section: Introductionmentioning
confidence: 99%